A Survey of Open Data Platforms in Six UK Smart City Initiatives. (17th August 2018) - Ghahremanlou, Lida; H Tawil, Abdel-Rahman; Kearney, Paul; Nevisi, Hossein; Zhao, Xia; Abdallah, Ali
Abstract: This paper presents a comparative analysis of the feasibility studies submitted by six UK cities (London, Birmingham, Manchester, Glasgow, Bristol and Milton Keynes). The datasets were collected during the period of February–March 2017 by exploring their Open Data resources, common visions of their smart programmes and the themes of their projects. The aim of this work is to raise awareness and access of the existing data resources, encourage alignment of data collection and curation among projects with compatible objectives in different cities and to identify the gaps in coverage that are hampering achievement of the cities' visions. In this research, we distinguish between stored datasets that are accessible via data hubs, and live data that are only accessible via application programming interfaces in real time. Given that our findings are purely based on stored Open Data, we conclude that the Smart City dream will be only achieved in reality, where those involved in Smart Cities-related projects co-operate and share both experiences and resources in order to maximize progress towards the common goal but to minimize duplication of efforts and repetition of the same mistakes.